Antioxidant Activity and Biocompatibility of Fructo-Polysaccharides Extracted from a Wild Species of Ornithogalum from Lebanon - Mohammad Kazem Medlej; Cherri Batoul; Hamza Olleik; Suming Li; Akram Hijazi; Ghassan Nasser; Marc Maresca; Céline Pochat-Bohatier (MDPI AG, 2021)
The present study aims to investigate the properties of biopolymers extracted from a Lebanese onion non edible plant. The extraction was performed under mild conditions by varying the percentage of ultra-sound (US) treatment duration to a total extraction time of 30 min (0, 50, 100% US). The extracts were characterized using FTIR, SEC, GC-MS, TGA, and DSC analyses. The composition of the extracts was determined from the total carbohydrate content and protein content measurements. The thermal analyses indicate that all samples have high thermal stability. The antioxidant activities of the extracts were investigated, using β-carotene bleaching, scavenging activity of ABTS, metal chelating ability, and total antioxidant activity tests. The results indicate that the 50% US treatment leads to the best antioxidant activity. Biocompatibility of the extracts was evaluated using hemolysis and cytotoxicity assays. The results showed that 0 and 50% US samples are not toxic to human cells, in contrary to 100% US.